1979
DOI: 10.1007/bf00492216
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of central and systemic administrations of nicotine in the rat

Abstract: Nicotine (0.16--0.50 mg/kg, SC) was found to exert a potent antinociceptive action on thermal stimuli as measured by the tail-flick test. This antinociceptive action of nicotine could be blocked by centrally active nicotinic or muscarinic blockers implicating both classes of cholinergic receptors in this effect. Quaternary blockers, however, failed to prevent nicotine-induced antinociception. This finding, together with the ability of small doses of nicotine (25 micrograms) to induce potent antinociceptive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(72 citation statements)
references
References 14 publications
2
68
0
2
Order By: Relevance
“…Hyperalgesia and͞or irritation have been observed after central injections of nicotinic agonists (8)(9)(10), systemic injections of subanalgesic doses (11), and intrathecal applications (12,13). This intrathecal effect is associated with significant increases in excitatory transmitter release (14), and both nicotinic and glutamate receptor antagonists can decrease this hyperalgesia (15,16).…”
mentioning
confidence: 99%
“…Hyperalgesia and͞or irritation have been observed after central injections of nicotinic agonists (8)(9)(10), systemic injections of subanalgesic doses (11), and intrathecal applications (12,13). This intrathecal effect is associated with significant increases in excitatory transmitter release (14), and both nicotinic and glutamate receptor antagonists can decrease this hyperalgesia (15,16).…”
mentioning
confidence: 99%
“…nAChRs are extensively distributed in central nervous system (CNS) and peripheral sites. Although most reports focus on the central sites of the analgesic action of nicotinic agonists (Damaj et al 1998, Khan et al 1994, Sahley and Berntson 1979, α-7 nAChRs were found in peripheral sites, such as ganglion neurons of the dorsal root (Boyd et al 1991, Hu and Li 1997, Genzen et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…But inflammatory reactions in peripheral tissues and action change in dorsal root of spine are the main reasons of delayed phase. The main reason of pain in second phase is because of inflammatory reactions (Sahley and Berntson, 1979;Shibata et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study have shown that MC extract can induce analgesia in mice. Also, it shows that MC has analgesic effects in both phases of formalin test that indicate that MC could have central nervous system (CNS) and local effects (Aceto et al, 1980;Murray and Brater, 1993;Phan et al, 1973;Sahley and Berntson, 1979). Studies on laboratory animals have shown that MC extract has antiinflammatory, antispasmodic and antidisquiet effects that are predicted in traditional medicine (Besson and Chaouch, 1987;Viola et al, 1995).…”
Section: Discussionmentioning
confidence: 99%